Research on AI-Based Intelligent Education of Tai Chi - Duan, Banxiang; Li, Yuchen; Li, Lintao; Ma, Qi; Fang, Wencai; Jiang, Xinyi; Liang, Qixing (2025 IEEE 3rd International Conference on Image Processing and Computer Applications (ICIPCA), 2025)
This study integrates artificial intelligence and virtual human technologies to create an intelligent Tai Chi education system that offers personalized teaching. It aims to tackle the challenges of limited teaching resources and the difficulty of personalized instruction in traditional Tai Chi education. The AI-based system provides customized teaching plans based on user characteristics and needs, significantly improving teaching efficiency and quality. Technically, the system uses AI algorithms for automated error correction, detecting incorrect movements and offering standardized guidance to ensure correct Tai Chi forms. It continuously monitors user movements, triggering an error-correction mechanism to provide precise feedback. By combining deep learning with ensemble algorithms (lightweight OpenPose, PoseFlow, and AlphaPose), the system precisely tracks and evaluates movements from multiple dimensions, including standardization, fluency, and coherence. This scoring system offers immediate feedback and helps correct errors through posture comparison and intelligent guidance, enhancing learning outcomes. Studies globally have shown that AI can precisely assess and guide sports skills through real-time movement analysis and feedback. As AI rapidly develops in sports education, its integration into teaching has become crucial for enhancing student participation and teaching quality. Against this backdrop, this study aims to promote the inheritance and innovation of Tai Chi culture through technological means and to promote traditional Chinese culture. By integrating AI technology with Tai Chi teaching, the study provides an efficient and personalized learning experience, stimulates interest in AI, and broadens its application in cultural education.